Å bli vaksinert, eller ikke å bli vaksinert, er det (det eneste) spørsmålet? - Jansen, Karine Aasgaard (Tidsskrift for kulturforskning, 2018)
In this article I examine Norwegian lay people’s attitudes towards vaccination with the 2009-2010 swine flu pandemic as a case study. During the pandemic the Norwegian public health authorities recommended mass vaccination as a main strategy for preventing infection. Vaccination is at present voluntary in Norway, but almost 45 per cent of the population were vaccinated against swine flu, including 600 000 children. 70 of these children have since developed narcolepsy as a side effect of the swine flu vaccine Pandemrix. Although these cases appear to have had little effect on the vaccine uptake in the public vaccination program which continues to remain high, many Norwegians still express scepticism to new vaccines. By drawing on a rather heated mediatized debate between so-called vaccine supporters- and opponents in 2015, 196 responses to a qualitative questionnaire and interviews with 17 public health stakeholders, the article focuses on lay people’s own thoughts regarding whether to vaccinate or not. In most cases, such reasoning can neither be described as being supportive of nor opposed to vaccination, but rather something in-between, depending on the vaccine in question.